Peristiwa Alih Kode dan Campur Kode Bahasa pada Masyarakat Pesisir Pelabuhan Ratu, Sukabumi - Hidayat, Gilang Ramadhan Putra; Raihan, Muhammad; Gunawan, Nurul Azizah Juliyani; Mupaqih, Tarisha Terreste; Pramudita, Tanaya Athifa; Cholif, Aditya; Sitaresmi, Nunung (Aksara: Jurnal Bahasa dan Sastra, 2025)
This study aims to analyze code switching and code mixing events in the coastal community of Pelabuhan Ratu, Sukabumi, West Java. Using a descriptive-qualitative research method, data were collected through observation and semi-structured interviews with research subjects, namely fishermen and traders around Pelabuhan Ratu. The data samples were 4 fishermen at the Fish Auction Market and 2 traders at the Traditional Market. The results showed that there were 21 internal code switching events with 18 events in fishermen and 3 events in traders. The significant difference in frequency between the code switching data of fishermen and traders was caused by differences in the background of the research subjects. This affected the speech of indigenous fishermen so that many code switching events occurred, while traders were indigenous people who had lived in Pelabuhan Ratu for a long time. Meanwhile, 37 code mixing events were found consisting of 4 code mixing in the form of words, 22 code mixing in the form of phrases, and 11 code mixing in the form of clauses. Based on these data, code switching events generally occur when speakers adjust their language to their conversation partners, while code mixing occurs because of the speaker's habit of mixing the use of Indonesian and Sundanese in everyday conversation. This study implies that the coastal community of Pelabuhan Ratu is a bilingual community that actively uses Indonesian and Sundanese in everyday communication. This finding can contribute to the development of sociolinguistic studies in other coastal areas. In addition, it can also be a suggestion and input for educational institutions to develop policies on the use of Indonesian in public spaces and the maintenance of local languages in the Pelabuhan Ratu area.Keywords: code switching, code mixing, bilingual speakers, coastal community linguistics, language maintenance